ICT Kit in Mathematics - Chaurasia, P.K. (JOURNAL OF INDIAN EDUCATION, 2012)
The role of ICT in the mathematics curriculum is much more than simply a passing trend and it is envisaged not simply as a technical skill or as a means of improving learning effectiveness but also as a way of transforming the goals and processes of education. It provides a real opportunity for teachers of all stages and subjects to rethink fundamental pedagogical issues alongside the approaches to learning that students need to apply in classrooms. Innovations that require teachers to change many aspects of their daily routines are very demanding for them. Complex innovations can only be successful if a number of interacting conditions are met. This paper describes a design for an ICT based tool which can be fitted in mathematics teachers’ daily routine easily. Though every teacher has her own style, this paper provides a comprehensive technology exposure along with how to design digital content resources using open source mathematical software with the pedagogical approaches and an evaluation mechanism through ICT. This ICT Kit in mathematics describes a design of a source for teacher’s professional development in mathematics as well as rubrics based continuous and comprehensive evaluation tool.